2018
DOI: 10.1186/s12913-018-3778-2
|View full text |Cite
|
Sign up to set email alerts
|

Using the behavior change wheel to identify barriers to and potential solutions for primary care clinical guideline use in four provinces in South Africa

Abstract: BackgroundClinical practice guidelines risk having little impact on healthcare if not effectively implemented. Theory informed, targeted implementation may maximise their impact. Our study explored barriers to and facilitators of guideline implementation and use by South African primary care nurses and allied healthcare workers in four provinces in South Africa. We also proposed interventions to address the issues identified.MethodsWe used qualitative research methods, comprising focus group discussions using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…These views mirrored those of PHC providers in the same districts that we spoke to who described that they would be more likely to use CPGs if digital access was possible. 32 However, like the managers, they perceived lack of internet in facilities, and exorbitant costs of data required for downloading CPGs, asbarriers to digital access. 32 Human resource constraints, such as clinical workload and understaffing, was another health system issue hindering CPG implementation, a finding that echoes a substudy of PHC clinical staff in these districts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These views mirrored those of PHC providers in the same districts that we spoke to who described that they would be more likely to use CPGs if digital access was possible. 32 However, like the managers, they perceived lack of internet in facilities, and exorbitant costs of data required for downloading CPGs, asbarriers to digital access. 32 Human resource constraints, such as clinical workload and understaffing, was another health system issue hindering CPG implementation, a finding that echoes a substudy of PHC clinical staff in these districts.…”
Section: Discussionmentioning
confidence: 99%
“…We used qualitative methods from an interpretative paradigm to understand the experiences and perspectives of provincial and district managers responsible for primary care guideline implementation. The methods and study context have been described in detail elsewhere, 32 and thus only a summary is provided here, together with a detailed description of the participants and analysis methods used.…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Behaviour Change Techniques are the active, observable and replicable components that make up an intervention. COM-B/BCW have been used successfully for behavioural analysis and to design interventions in both health and non-health-related elds [26,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], but to our knowledge, has been used in only one study of TB on contact tracing in a low-resource setting, to identify barriers and facilitators and to tailor interventions to improve contact investigation in Kampala [26]. In the qualitative arm, to understand the challenges in recognising and testing for TB in admitted children we analysed data from: i) semi-structured interviews, small-group discussions and key informant interviews with front line health workers and mid-level managers; ii) observations of TB trainings, sensitisation meetings, policy meetings, and hospital practices, and iii) desk review of guidelines, job aides and policy documents, which have been reported elsewhere [31].…”
Section: Using the Behaviour Change Wheel To Guide Intervention Designmentioning
confidence: 99%